“If You Call Yourself a Jew”: A Reconsideration on Identifying Paul’s Interlocutor(s) in Romans 2 - Storbakken, Scott (Religions, 2024)
In Romans 2, Paul uses the Greco-Roman rhetorical technique of diatribe, i.e., a debate with a fictional partner. Reformation interpreters insisted that Paul confronts a hypocritical Jew; this thought remained prominent until the last century and has yielded unintentional anti-Semitic readings of Paul in many Protestant circles to this day. The New Perspective tempered the problem by suggesting that Paul begins the passage opposing a gentile until verse 17 when he has a new, Jewish interlocutor. However, Paul’s language gives no indication of a shift. Scholars of the Radical New Perspective have attempted to solve this language challenge by claiming that Romans 2 contains a single diatribe with a gentile opponent. Although this paper agrees with that basic conclusion, it proposes a new specific identity for that interlocutor that departs from the general consensus of the Radical New Perspective. That consensus identifies the interlocutor as a gentile Judaizer. No scholars, however, have clearly displayed the existence of such people at the time when Paul wrote Romans. On the other hand, Paul’s letter constantly attacks beliefs of gentile supersession, implying that some audience members might entertain such presumptions. This essay, therefore, proposes that Paul debates a single gentile supersessionist.